Work-Life Integration vs Work-Life Balance : Tracing Generation Z's Preferences and Perceptions of Flexible Work Patterns in a Creative Startup Environment - Sakinah, Sakinah (Westscience Press, 2025)
In the work landscape in the modern world, it is increasingly digitized and the change in the work paradigm in the current digital era has given rise to new work patterns and the main approach to how Generation Z manages their professional and personal lives; Work-Life Balance and Work-Life Integration. This study aims to explore and examine the preferences and perceptions of Generation Z towards new work patterns, especially in the context of creative industry startups. By using qualitative methods and data obtained from interviews with Gen Z employees in several creative industry startup companies in Jakarta. From the results of the study, it was identified that the majority of Generation Z employees are more likely to choose Work-Life Integration preferences, which they consider to be more in line with lifestyle and lifestyle in this digital era. Such as the lifestyle of Generation Z in the use of technology that they can access and have and how they combine personal and professional activities. However, in practice, it is found that there is a need for clear and healthy boundaries so that this flexibility does not lead to work burnout, this study highlights how important the role of company management is in creating a balanced, supportive and adaptive work environment and policies that are supportive and adaptive to the needs of Gen Z which is certainly oriented towards the sustainability of young employee productivity.